Epidemiological-Clinical Profile and Magnetic Resonance Imaging (MRI) of Endometriosis in Kinshasa (2022–2023) - Mbambi, Félix Dibazola; Bukumba, Cynthia Minouche; Tongo, Stéphane Yanda; Letumu, Nodi Botshele; Tshienda, Frederick Tshibasu; Mazoba, Tacite Kpanya; Boloweti, Doudou Batumbo; Ifinji, Richard Ekila; Simanyama, Pierre Lwamba; Aundu, Antoine Molua; Mukaya, Jean Tshibola; Mvila, Gertrude Luyeye (Orapuh Journal, 2025)
Introduction Endometriosis is a chronic, often underdiagnosed gynaecological condition affecting women of reproductive age, with a growing impact on quality of life and fertility worldwide. Despite its prevalence, limited data are available in sub-Saharan African settings, including Kinshasa.Purpose To describe the epidemiological, clinical, and MRI features of endometriosis in women undergoing pelvic MRI in Kinshasa between 2022 and 2023.Methods A retrospective descriptive cross-sectional study was conducted using records from three MRI centres in Kinshasa. Data were collected from patients with a clinical or ultrasound suspicion of endometriosis and an MRI-confirmed diagnosis. Variables analysed included age, clinical presentation, MRI indications, protocols used, and forms of endometriosis identified.Results A total of 83 women were included, with a mean age of 37 ± 9 years. Most patients (58%) were aged between 20 and 40 years. The predominant clinical presentations were chronic pelvic pain and infertility (53%), followed by dysmenorrhoea and menstrual disorders (22%). MRI was most frequently requested for suspected endometriosis (65%). Adenomyosis was the most common form observed (40%), particularly in women over 40, while ovarian endometriosis accounted for 20% of cases. Deep pelvic endometriosis was more frequent in women under 25. Vaginal and rectal opacification with contrast was used in 43% of cases, mostly when performed by general radiologists.ConclusionEndometriosis is prevalent among women of reproductive age in Kinshasa, with chronic pelvic pain and infertility as key presenting complaints. MRI remains a valuable diagnostic tool, especially for detecting adenomyosis and ovarian endometriosis. These findings emphasise the importance of improved diagnostic strategies and awareness in low-resource settings.